Pengaruh Pemahaman Nilai-Nilai Pancasila terhadap Kehidupan Berdemokrasi Mahasiswa - Ciciria, Deri; Kesuma, Tubagus Ali Rachman Puja; Hafidz, Muhammad (Tapis: Jurnal Penelitian Ilmiah, 2022)
Higher education must become a strategic ecosystem in developing Pancasila values ​​to regenerate student democratic life. The purpose of this study was to find out and describe the influence of understanding Pancasila values ​​on the democratic life of STKIP PGRI Bandar Lampung students. This research involved 358 students spread across 7 (seven) study programs. This research is a quantitative descriptive study using the correlational method. The instrument of Pancasila values ​​was adopted from the embodiment of the socialization material "Four Pillars of National and State Life", while the instrument for democratic life was adopted from the embodiment of Udin S Winataputra's opinion. Prerequisite tests and data analysis techniques in this study were carried out with the help of the SPSS version 25 application. The results showed a significant influence between the understanding of Pancasila values ​​on the democratic life of STKIP PGRI Bandar Lampung students with a correlation value of 0.538. This research proves that college students fulfill the requirements as interest groups and legitimate democratic actors. The involvement of students in social projects and problem-solving provides more opportunities to develop students' fighting power and critical power. This will further enhance students' understanding of Pancasila values ​​which will ultimately improve students' democratic life. The trilogy of success in learning student democratic behavior focuses on the relationship between learning in the classroom, the importance of student autonomy, and the development of democracy played by the government.